I believe in the Holy Spirit: Power and technology at crossroads - Kelebogile T. Resane (African Journal of Pentecostal Studies)
Background: This year, 2025, Christians from all persuasions (Catholic, Orthodox or Protestant) commemorate 1700 years of Nicene Creed, referred to as Creed henceforth. The problem addressed here is that Pentecostals confess their belief in the Holy Spirit but are not aware of the history of this confession.